(untitled) (SCIENCE TIME JOURNAL, 2026)
Critical thinking has become one of the most essential skills in modern education, particularly in English as a Foreign Language (EFL) classrooms. Debate activities provide learners with opportunities to analyze information, express opinions, defend arguments, and evaluate opposin viewpoints. This article examines the role of debate activities in developing critical thinking skills during English lessons. The study explores methodological approaches to implementing debates in EFL classrooms and analyzes their impact on learners’ communication abilities and analytical thinking. The findings indicate that debate-based instruction enhances students’ speaking confidence, logical reasoning, collaboration, and problem-solving skills. The article also provides practical recommendations for English teachers who aim to integrate debate activities effectively into classroom practice.